2012
DOI: 10.1128/aem.00001-12
|View full text |Cite
|
Sign up to set email alerts
|

Historical and Recent Achievements in the Field of Microbial Degradation of Natural and Synthetic Rubber

Abstract: This review intends to provide an overview of historical and recent achievements in studies of microbial degradation of natural and synthetic rubber. The main scientific focus is on the key enzymes latex-clearing protein (Lcp) from the Grampositive Streptomyces sp. strain K30 and rubber oxygenase A (RoxA) from the Gram-negative Xanthomonas sp. strain 35Y, which has been hitherto the only known rubber-degrading bacterium that does not belong to the actinomycetes. We also emphasize the importance of knowledge of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
46
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(54 citation statements)
references
References 51 publications
1
46
0
Order By: Relevance
“…Lcp is widespread in Gram-positive rubber degraders and is unrelated to RoxA; Lcps have a significantly different molecular mass of about 42 kDa, compared to Ϸ72 kDa for RoxAs. The amino acid sequences of Lcps have no heme binding motifs that could serve as covalent attachment sites for heme groups, and Lcps cleave rubber to larger degradation products than RoxAs (6,15,16). Recently, the Lcp proteins of two species (Streptomyces sp.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Lcp is widespread in Gram-positive rubber degraders and is unrelated to RoxA; Lcps have a significantly different molecular mass of about 42 kDa, compared to Ϸ72 kDa for RoxAs. The amino acid sequences of Lcps have no heme binding motifs that could serve as covalent attachment sites for heme groups, and Lcps cleave rubber to larger degradation products than RoxAs (6,15,16). Recently, the Lcp proteins of two species (Streptomyces sp.…”
mentioning
confidence: 99%
“…Most of these materials are released to the environment in the form of waste or by abrasion in the case of tires. As a natural compound, rubber is a fully biodegradable material, and many rubber-degrading microorganisms have been isolated from various ecosystems in the past (1)(2)(3)(4)(5)(6)(7)(8). The initial step of rubber biodegradation is the enzymatic cleavage of the polymeric carbon backbone to smaller products.…”
mentioning
confidence: 99%
“…Isolate F5 and F7 were identified as Gram-positive and others were Gram-negative bacteria. All ten isolates did not produce clearing zone around the colonies indicated that they could degrade the latex concentrate by a production of an intracellular enzyme [16].…”
Section: A Isolation Of Rubber-degrading Microorganisms From Soil Samentioning
confidence: 99%
“…These polymers can be used in thousands of ways i.e. in the fabrics, mining, power generation, agriculture, transportation, paper industries, insulation of cables, wires, and various equipments, in addition, it is the major component in rubber tires [16]. However, billions of discarded tires are currently stockpiled around the world and these are increasing exponentially and causing important environmental problems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation